Association of polymorphisms rs2303729, rs10880, and rs1131620 of LTBP4 with sarcopenia in elderly patients with type 2 diabetes mellitus. (17th November 2022) - Ibarra-Tapia, Ingrid Yali; Juárez-Sandoval, Ariadna; Pérez, Itzel Torres; Cano-Martínez, Luis Javier; Sánchez-García, Sergio; Ruiz-Batalla, Juana Marlen; Aroche-Reyes, Irma Angélica; García, Silvia; Canto, Patricia; Mejía, David-Rojano; Coral-Vázquez, Ramón Mauricio
Abstract: Background: Latent TGFβ binding protein 4 ( LTBP4 ) modifies skeletal muscle function, and polymorphisms in this gene have been associated with a longer ambulation time in patients with Duchenne muscular dystrophy. However, no studies associate these polymorphisms with an acquired muscle condition. Aim: The study aims to determine whether three functional variants within the LTBP4 were associated with sarcopenia in patients with type 2 diabetes mellitus (T2DM). Subjects and methods: We performed an analysis with 144 elderly individuals with T2DM, including 101 without sarcopenia and 43 with sarcopenia. Polymorphism frequency was determined by real-time PCR allelic discrimination TaqMan assay. Results: Under different genetic models, the univariant analysis did not show a significant association of any polymorphism with sarcopenia. But the multivariate model analysis showed that variant rs1131620 (OR 7.852, 95% CI 1.854-33.257, p = 0.005) was significantly associated with sarcopenia under a dominant model. Under the same analysis, the variants rs2303729 and rs10880 had a more discrete association (OR 3.537 95% CI 1.078-11.607, p = 0.037; OR 5.008, 95% CI 1.120-22.399, p = 0.035, respectively). Conclusions: Our study highlights the importance of studying LTBP4 polymorphisms associated with sarcopenia. These findings suggest that the rs1131620 polymorphism of the LTBP4 may be part of the observed sarcopenia process in patients with T2DM.